The Place of Samoobrona RP in the Typology of Political Parties - Lisiakiewicz, Rafał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Samoobrona RP (Self-Defence of the Republic of Poland), headed by its charismatic leader, Andrzej Lepper, was one of the most interesting parties on the Polish political scene throughout the first decade of the 21st century. Its success and ultimate collapse can be attributed to the political situation in Poland, the party’s unique political appeal and the way it conducted itself – all factors that make it difficult to classify the party. In this article the author shines a light on the fundamental problems concerning the typology of Samoobrona RP